ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYUSUNAN ANGGARAN BERBASIS KINERJA PADA PEMERINTAH DAERAH KABUPATEN DELI SERDANG - Rinadiantika, Septy; Mariyam, Mariyam (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to analyze the factors that influence the preparation of the budget for the regional income and expenditure budget realization report at the Regional Government of Deli Serdang Regency. The type of research is causal research, this research seeks to determine the relationship between the independent variable and the dependent variable through testing hypotheses that have been previously formulated. The population in this study were all employees/employees working in Deli Serdang Regency who were selected using a purposive sampling technique with the number of samples used in this study totaling 46 people. There are three independent variables in this research, namely Commitment (X1), Administrative System (X2), Human Resources (X3). The analysis in this research was carried out to test the hypotheses that have been established. The tool used is the Multiple Linear Regression Test with the help of SPSS version 23. The results of this research show that there is an influence of Organizational Commitment, Administrative Systems, Human Resources on the Budget Realization Report in the regional government of Deli Serdang Regency.